The Students’ Interest in Learning Intercultural Communication Using The Integration of Mobile Learning Technology - Saiful (ETDC: Indonesian Journal of Research and Educational Review, 2023)
The objective of this study is to describe students' interest in learning intercultural communication through local wisdom, specifically Makassar ethnicity, integrated with mobile learning technology. This study uses a quantitative descriptive method. The researchers chose one class, which consisted of 27 students in the English Education Department at Muhammadiyah University of Makassar. The researchers used two research instruments, namely questionnaires and documentation. With the following process: Creating questions After creating questions for the questionnaire, the researcher comes to class and distributes participant questionnaires. The researcher gives students 30 minutes to answer the questionnaire, adding up the plated questionnaire data. Data analysis was carried out through descriptive analysis by calculating the frequency, mean score, percentage, and average using SPSS. From the results of the descriptive analysis, it is known that the average score of interest in learning intercultural communication through the local wisdom of Makassar Ethnic using mobile learning integration is 74.55, which indicates that there is a lot of interest. This outcome is similarly related to the average percentage of survey responses, where 35.49% of students said that they were interested. This means that students in the English Education Department of Muhammadiyah University of Makassar are interested in learning English intercultural communication through the local wisdom of Makassar ethnicity.